Comparison of ventilatory restriction in techniques of respiratory physiotherapy and changes of position - Kock, Kelser de Souza; Paz, Camila Mendes Flor; Faraco, Cindy Maximiano; Onofre, Fernando Rodrigues; Souza, Laís Bruna Ávila de; Meneguel, Mirian (Manual Therapy, Posturology & Rehabilitation Journal, 2015)
Introduction: Body position affects the respiratory mechanics and could be favorable to pulmonary function when combined with respiratory physiotherapy. Objective: Was to compare the ventilatory restriction in respiratory therapy techniques and changes of position. Method: For analysis of lung volume was measured Slow Vital Capacity (SVC) in university students in the positions: sitting, dorsal decubitus (DD), DD with application of maneuver thoracic blockade of the right hemithorax and right lateral decubitus (RLD). In all maneuvers were instructed to perform an inspiration to total lung capacity and slow exhalation to residual volume. Results: It was evaluated 26 subjects with a mean age of 25.5 ± 11 years and mean body mass index of 25 ± 4 kg/m 2 . The values obtained from SVC sitting, DD, DD with blockade and DLD were respectively 3.5 ± 1.5 liters (87.7 ± 26.8%); 2.9 ± 1.4 liters (75.0 ± 26.5%); 3.0 ± 1.4 liters (75.2 ± 26.2%); 3.5 ± 1.6 liters (88.3 ± 29.4%). Using the SVC in a sitting position as compared, there was no statistical difference in DD (p = 0.024) and DD with position blockade (p = 0.036). There was no significant difference in the DLD (p = 0.459) position. Conclusion: Can conclude that the positions DD and DD with blockade reduced lung volume, whereas DLD position showed no significant difference when compared to sitting position, suggesting that this position is an option favorable position for respiratory therapy.